Diversity and Inclusion Activities in Database Conferences: A 2021 Report. - Amer-Yahia, Sihem; Amsterdamer, Yael; Bhowmick, Sourav S.; Bonifati, Angela; Bonnet, Philippe; Borovica-Gajic, Renata; Catania, Barbara; Cerquitelli, Tania; Chiusano, Silvia; Chrysanthis, Panos K.; Curino, Carlo; Darmont, Jérôme; et al. (SIGMOD Record, 2022)
Diversity and Inclusion (D&I) are core to fostering innovative thinking. Existing theories demonstrate that to facilitate inclusion, multiple types of exclusionary dynamics, such as self-segregation, communication apprehension, and stereotyping and stigmatizing, must be overcome [11]. A diverse group of people tends to surface different perspectives, which help to understand and address D&I. Fostering D&I in research communities must address issues related to inclusive interpersonal and small group dynamics, rules and codes of conduct, increasing diversity in under-represented groups and disciplines, and organizing D&I events, and longterm efforts to champion change [15].